2020
DOI: 10.7150/jca.41039
|View full text |Cite
|
Sign up to set email alerts
|

Precise right hemihepatectomy for the treatment of hepatocellular carcinoma guided by fusion ICG fluorescence imaging

Abstract: To evaluate the clinical significance of fusion indocyanine green (ICG) fluorescence imaging in precise right hemihepatectomy for the treatment of hepatocellular carcinoma (HCC). 47 patients with HCC who underwent right hemihepatectomy were retrospectively analyzed. 18 of them guided by fusion ICG fluorescence imaging (FIGFI) while 29 patients underwent conventional right hepatectomy without guidance. Compared to the patients with conventional treatment, the intraoperative blood loss of the patients with guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…When combined with preoperative 3D reconstruction and IOUS, it can be solid real-time navigation tool to make a huge difference in accuracy of liver resections. However, best time point and dose of ICG administration for tumor identification and liver segmentation remains unclear due to various patient backgrounds and imaging settings in the previous studies 56–101 . Thus, its administration strongly needs to be tailored case by case in daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…When combined with preoperative 3D reconstruction and IOUS, it can be solid real-time navigation tool to make a huge difference in accuracy of liver resections. However, best time point and dose of ICG administration for tumor identification and liver segmentation remains unclear due to various patient backgrounds and imaging settings in the previous studies 56–101 . Thus, its administration strongly needs to be tailored case by case in daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…No matter which staining method is used, the ultimate goal is to distinguish the resected and the retained liver tissue according to the anatomical structure and to guide the operator to better perform anatomical liver resection. Our previous result also suggested that there is no significant difference between positive and reverse stains during liver resection ( 41 ).…”
Section: Discussionmentioning
confidence: 68%
“…With the negative-staining technique, reported in 36 publications, ICG was predominantly used as an absolute dose of 2.5 mg or as 0.25–0.5 mg/kg. Advantages of using fluorescence imaging for hepatic segmentation for enhancing operative outcomes (operation time,23 blood loss,20 23–25 postoperative bile leaks26 and cancer curability23 25 26) have been documented in several controlled studies.…”
Section: Resultsmentioning
confidence: 99%
“…Since fluorescence imaging enables surgeons to visualise targeted hepatic segments with higher signal-to-background ratios than the naked-eye examinations and standard white-light imaging used with conventional techniques,46 47 the number of publications on both of these newer techniques has increased dramatically in the past 3 years. The expected role of fluorescence-guided hepatic segmentation is to aid the accurate identification of intersegmental planes during hepatectomy procedures which, in turn, should enhance surgical outcomes like operation time, the incidence of complications associated with bile leaks and ischaemia in the remnant liver and tumour-free surgical margins, as suggested by previous prospective studies 20 23–26. The negative-staining technique is simple to perform, while the feasibility of the positive-staining technique seems to be improved by employing preoperative puncture before insufflation48 and intracorporal puncture by robotic manipulation 49.…”
Section: Discussionmentioning
confidence: 99%